Infección por Brucella canis en humanos: propuesta de un modelo teórico de infección a través de la ruta oral (2013)
ABSTRACT: Brucella canis infection in humans has recently been recognized as a zoonosis, but it is frequently under reported because the flu-like symptoms are often confused with the presence of other disease-causing pathogens. Dogs are the primary hosts for Brucella canis; the increasing trend to adopt dogs as pets also enhances the likelihood of transmission of Brucella canis infection through contact between infected dogs and owners. In Colombia, there are reports of isolates of B. canis from kennel dogs and also from one human being along with seropositive results from dogs and humans. However, the mechanism of hostpathogen interactions leading to the infection of Brucella canis in dogs is still unknown and even less is known about human infections. This review proposes a model for human infection with Brucella canis through the oral route. We use the information available for other human-infecting Brucella species, including B. abortus and B. melitensis, which differ from B. canis in the structural composition of the lipopolysaccharide molecule. The mechanism of cellular infection used by B. canis to invade and establish infection in nonphagocytic and phagocytic cells is also hypothesized.